Endoscopic orbital decompression for Graves′ orbitopathy - Priti Lal; Alok Thakar; Nikhil Tandon (Indian Journal of Endocrinology and Metabolism, 2013)
Aim: To study the efficacy of endonasal endoscopic orbital decompression in cases of Graves′ orbitopathy. Material and Methods: A total of 24 orbits in 12 patients underwent endoscopic orbital decompression for graves orbitopathy in the period between October 2002 and December 2010. Indications for surgery included proptosis, corneal exposure, keratitis, and compressive optic neuropathy. Decompression was accomplished by the removal of the medial and part of inferior wall of the orbit and slitting of the orbital periosteum. Pre and postoperative exophthalmometry measurements and visual acuity were recorded and compared. Results: A mean orbital regression of 3.70 mm was noted following endoscopic decompression. The visual acuity improved significantly in one of two eyes decompressed for failing visual acuity secondary to optic nerve compression. Transient diplopia was invariable following surgery but resolved over the next 8 weeks. One case manifested unilateral frontal sinus obstruction symptoms 4 months postoperatively and responded to medical therapy. Conclusion: Endonasal endoscopic orbital decompression provides for an effective, safe, and minimally invasive treatment for proptosis and visual loss of Graves Orbitopathy. Long-term problems with diplopia were not noted in the endonasal endoscopic approach for orbital decompression.